Optimization and Mechanistic Characterization of Pyridopyrimidine Inhibitors of Bacterial Biotin Carboxylase - Andrews, Logan D. (J Med Chem, 2019)
A major challenge for new antibiotic discovery is predicting the physicochemical properties that enable small molecules to permeate Gram-negative bacterial membranes. We have applied physicochemical lessons from previous work to redesign and improve the antibacterial potency of pyridopyrimidine inhibitors of biotin carboxylase (BC) by up to 64-fold and 16-fold against E. coli and P. aeruginosa, respectively. Antibacterial and enzyme potency assessments in the presence of an outer membrane permeabilizing agent or in efflux-compromised strains indicate that penetration and efflux properties of many redesigned BC inhibitors could be improved to various extents. Spontaneous resistance to the improved pyridopyrimidine inhibitors in P. aeruginosa occurs at very low frequencies between 10(−8) to 10(−9). However, resistant isolates had alarmingly high MIC shifts (16 to >128-fold) compared to the parent strain. Whole genome sequencing of resistant isolates revealed that either BC target mutations or efflux pump overexpression can lead to the development of high-level resistance.